DISTRIBUTION AND PRODUCTIVITY OF LABOR ON AGRICULTURAL BUSINESS: EMPIRICAL STUDIES AT CHILI FARMING - Jaya, Adisa Putra; Darwanto, Dwidjono Hadi; Waluyati, Lestari Rahayu (Jurnal Aplikasi Manajemen, 2019)
Chili is classified as a commodity with high economic value and intensive labor absorption. The needs of farmworkerswere usuallygiven from labor in the household and labor outside the household of farmers by different distributions. The research aims to measure the utilization and distribution of labor in the cultivation of chili,determine the factors affecting the working time allocation of the labor in chili cultivation, and measure the feasibility of chili-based on labor productivity. This research was conducted in the Pakem District in Sleman D.I. Yogyakarta. The number of respondents selected in this study was 60 farmers. Thedesign of the study is descriptive analysis, use the Cobb-Douglas analysis functions and the analysis of the labor productivity index. The results showed that the allocation of working time on the farm was 49.70 HKP. Land factors and real wages are positively influential, while the education factor negatively affects the time of labor in the household. Chili cultivated in the Pakem District is feasible based on the productivity index. The Labor productivity index value is 2.81.